Strategi Pengelolaan Pembelajaran Isu Materi Sejarah â€œSerupaâ€ dan Sejarah Kontroversial - Djunaedi Bunglai (Jurnal Pendidikan Sejarah, 2015)
The purpose of this writing is to seek for the solution in the teacherâ€™s â€œproblemâ€ in managing Indonesian History as a regular subject and History Teaching as a special subject in accordance with 2013 Currriculum. That is because not only that two subjects contain the â€œsameâ€ scope of subjectâ€™s material, but also because those contain controversial history material substance.Based on the difference between the purpose of each subject, those are therefore offering the correct solution, which are the strategies in managing the â€œsameâ€ subjectâ€™s material history substance teaching based on Constructivistic-ColaborativeBy using those two strategies, not only that those solve the teacherâ€™s â€œproblemâ€ in implementing those two subjects, but also exploring studentâ€™s competence in accordance with each learning objectives